Comparison of the Effectiveness of Traditional Massage with and Without Lemongrass Aromatherapy in Alleviating Menopausal Symptoms - Susanti, Risqi Wahyu; Baeda, Abd. Gani; Tukatman, Tukatman (Fakultas Kedokteran, 2024)
Menopause is a natural phase experienced by all women, marked by the cessation of menstruation and often accompanied by symptoms of estrogen decline. With the increasing life expectancy of women, most will spend significant years in the menopausal phase, facing various physical and psychological symptoms that disrupt their quality of life. Objective: This study aims to compare the effects of traditional massage with and without the combination of lemongrass aromatherapy on menopausal symptoms.: This is a quasi-experimental study with a pretest and posttest design with two comparison treatments on 40 women aged 40-60 years, divided into two groups. The first group received traditional massage with lemongrass oil and lemongrass aromatherapy, while the second group received traditional massage with lemongrass oil only. Measurements were taken before and one week after the intervention, using the Menopause Rating Scale (MRS) to assess menopausal symptoms. Results: Menopausal symptom scores significantly decreased in both groups after the intervention. The aromatherapy massage group showed a decrease in the average symptom score from 14.80 to 5.60 (p=0.000), while the traditional massage group showed a decrease from 11.34 to 4.65 (p=0.000). The comparison between the two groups yielded a p-value of 0.197, indicating no significant difference in symptom score reduction, although the aromatherapy massage group experienced a greater decrease in menopausal symptoms than the massage-only group. There is no significant difference in the reduction of menopausal symptoms between the groups receiving massage with and without lemongrass aromatherapy; however, both interventions are equally effective in reducing menopausal symptoms. Further research is needed to increase the frequency of lemongrass aromatherapy massage.